Kvighotell - Johansson , Christoffer (SLU/Rural Buildings and Animal Husbandry (until 121231), 2009)
In this essay I have summarized important factors for an effective, but also successful, way to raise and house heifers. This study can be used for other dairy farms to use as guidelines in their process to raise heifers. To let outside heifer growers house, feed and have the heifers pregnant before return, can save a lot of work. But also moneywise, when the care and individual programs makes them strong and increases the growth. The result is a faster breeding and an earlier time for their first calving.